(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the best practices of Turkish prosecutor’s offices are highlighted, and the importance of information and communication technologies at the national level is discussed. In addition, the Law on Artificial Intelligence is mentioned separately, and the issues of its use and implementation in the Republic of Uzbekistan in the future are highlighted.